2012
DOI: 10.5664/jcsm.1906
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Obstructive Sleep Apnea Lower in Double Reed Wind Musicians

Abstract: Study Objectives: Obstructive sleep apnea (OSA) is caused by a collapse of the upper airway. Respiratory muscle training with a wind instrument (didgeridoo) in patients with moderate OSA has been previously shown to improve OSA symptomology. However, a survey of orchestra members did not indicate a difference in OSA risk between wind and non-wind instrumentalist. The present study examines whether playing of different wind instrument types may affect the risk of OSA. Methods: A national sample of active musici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 20 publications
0
35
1
1
Order By: Relevance
“…Furthermore, the instrument utilized may impact learnability and efficacy. Ward et al demonstrated in a nationwide survey study that rates of OSA were lower in double reed instrumentalists, but not in wind instrumentalists, compared to the general population . Although our findings suggest that native instrument resistance does not alter the oropharyngeal dynamics of the technique, there may be differences in therapeutic efficacy depending upon the instrument used.…”
Section: Discussioncontrasting
confidence: 77%
“…Furthermore, the instrument utilized may impact learnability and efficacy. Ward et al demonstrated in a nationwide survey study that rates of OSA were lower in double reed instrumentalists, but not in wind instrumentalists, compared to the general population . Although our findings suggest that native instrument resistance does not alter the oropharyngeal dynamics of the technique, there may be differences in therapeutic efficacy depending upon the instrument used.…”
Section: Discussioncontrasting
confidence: 77%
“…As age and years of practice were positively correlated, we assume that improvement of sleep-related respiration is due to the habitual playing of the WI and therefore, the increased training of the upper airway muscles. This has been indicated by survey studies investigating the digeridoo and double reed WI [14][15][16]. Our sample of WI players included four double reed instruments (oboe, bassoon), but also five other…”
Section: Sleep-related Respiration and Wind Instrumentsmentioning
confidence: 96%
“…While working conditions of professional musicians may negatively affect their sleep patterns, recent studies discovered that playing instruments that require use of certain muscles may have a positive effect on sleep-disordered breathing events [14][15][16]. Obstructive sleep apnea (OSA) is a chronic sleep-disordered breathing condition caused by recurrent upper-airway collapse during sleep [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hatásos lehet a naponta elvégzett pár perces uvula-, nyelv-, állka-pocs-és légcsőtorna, amely az izmok tónusának fokozása révén hosszú távon javítják az alvás közbeni átjárhatósá-got is [51]. Ilyen elven segíthet a fúvós hangszereken való játszás is [52], bár erre nem minden kutatásban találtak elegendő bizonyítékot.…”
Section: éLetmód-terápiaunclassified